Abhimanyu fights while breaking into the Chakravyuha - 54 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in Event description from Mahabharata : Abhimanyu, the son of Arjuna and Subhadra, is shown here fighting Drona while breaking into the Chakravyuha – a complex fighting formation with soldiers arranged in seven circles, an art he learnt while still inside his mother’s womb by listening to a conversation between Krishna and Subhadra. He, however, fell asleep when Krishna narrated the part of how to break out from inside. He was the only one from the Pandavas who knew how to break inside the formation, other than Arjuna. And thus, Abhimanyu could break in, but was killed (at the age of 16 years) while trying to break out.